Light‐emitting diode irradiation induces AKT/mTOR‐mediated apoptosis in human pancreatic cancer cells and xenograft mouse model. Issue 2 (4th August 2020) - Kim, Young Mi; Ko, Sung‐Hwa; Shin, Yong‐Il; Kim, Yeonye; Kim, Taehyung; Jung, Jaehoon; Lee, Sang‐Yull; Kim, Nam Gyun; Park, Kyoung‐Jun; Ryu, Ji Hyeon
Abstract: The beneficial effects of light‐emitting diode (LED) irradiation have been reported in various pathologies, including cancer. However, its effect in pancreatic cancer cells remains unclear. Herein, we demonstrated that blue LED of 460 nm regulated pancreatic cancer cell proliferation and apoptosis by suppressing the expression of apoptosis‐related factors, such as mutant p53 and B‐cell lymphoma 2 (Bcl‐2), and decreasing the expression of RAC‐β serine/threonine kinase 2 (AKT2), the phosphorylation of protein kinase B (AKT), and mammalian target of rapamycin (mTOR). Blue LED irradiation also increased the levels of cleaved poly‐(ADP‐ribose) polymerase (PARP) and caspase‐3 in pancreatic cancer cells, while it suppressed AKT2 expression and inhibited tumor growth in xenograft tumor tissues. In conclusion, blue LED irradiation suppressed pancreatic cancer cell and tumor growth by regulating AKT/mTOR signaling. Our findings indicated that blue LEDs could be used as a nonpharmacological treatment for pancreatic cancer. Abstract : Our study demonstrated that blue light‐emitting diode (LED) irradiation plays a critical role in promoting apoptosis of pancreatic cancer cells. For the first time, we demonstrated that the AKT/mTOR pathway that plays an important role in cell death is regulated by blue LED irradiation in human pancreatic cancer cells. Additionally, blue LED irradiation suppresses tumor formation and growth in an experimental xenograft tumor model via AKT2 protein expression inhibition. Therefore, these findings may have a positive effect on the treatment of pancreatic cancer by regulating AKT2 expression levels, which play a central role in the pathogenesis of pancreatic cancer.